Implementasi Metode Mind Mapping Berbasis Visualisasi Informasi Digital untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Sekolah Dasar - Usman Arfan; Muhammad Rizki Santoso (STMIK Pesat Nabire, 2026)
This study aims to improve students’ learning activities and learning outcomes in history learning through the implementation of a digital visual-based mind mapping method at SD Plus Asy-Syafi’iyah Nabire, Central Papua. This research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects consisted of 40 students. Data were collected through observation of students’ learning activities, learning achievement tests, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. The results indicated that the average score of students’ learning activities increased from 2.0 in the pre-cycle to 3.6 in the second cycle. In addition, the average learning achievement score increased from 62.4 in the pre-cycle to 83.6 in the second cycle, with classical mastery reaching 90%. These findings demonstrate that the digital visual-based mind mapping method is effective in improving students’ learning activities and learning outcomes in elementary school history learning.